Global research on submarine landslides, 2001–2020 - Chen, Wenwen; Xing, Junhui (Frontiers in Earth Science, 2023)
Submarine landslide as one of the hotspots in marine geoscience research, is one of the most harmful marine geological disasters which got a lot of attention. In order to understand the research status and future research directions of submarine landslides, this paper applied an analysis of global submarine landslide-related work during the period 2001 to 2020. To do this, Science Citation Index Expand (SCIE) and Social Sciences Citation Index (SSCI) belong to Web of Science Core Collection were the two bibliographic databases taken as a reference. In this study, we focused on document types, publishing languages, subject categories, productivity of journals, countries and author, and co-occurrence keywords network. Geoscience multidisciplinary, Geochemistry Geophysics, Oceanography, Environmental Sciences and Materials Science Multidisciplinary are five popular science categories in the past two decades. Marine Geology, Marine and Petroleum Geology and Journal of Volcanology and Geothermal Research are the three most productive journals on submarine landslides. Marine Geology is the most active journals among the all journals. The USA, the UK, China, Germany and France are the five most productive countries. At the institutional level, the Centre National De la Recherche Scientifique (CNRS, France) are the most active institution, followed by Chinese Academy of Sciences (China) and Helmholtz Association (Germany). Masson DG and Talling PJ from the UK contribute the most high-quality submarine landslides-related publications. Analyzing by CiteSpace, the five largest clusters on submarine landslides field are “gas hydrate”, “turbidity current”, “thin film”, “debris avalanche” and “submarine canyon”. Active future research directions of submarine landslides are “south china sea”, “slump” and “submarine mass failure”.